Períodos de interferência e controle químico de plantas daninhas na cultura do gergelim (Sesamum indicum L.) - Lins, Hamurábi Anizio (Universidade Federal Rural do Semi-Árido, 2018)
The sesame (Sesamum indicum L.) is an oilseed which presents great economic potential, due to the possibilities of exploration, both in the national market and in the international market, being adapted to the semi-arid conditions in several countries. The control of weeds in the sesame crop is a fundamental practice to ensure the high productivity of this oilseed. In this sense, it is important to define the critical period of interference prevention (PCPI) to achieve efficiency and low control costs. After defining the interference periods for the crop, the choice of the control methods that will be adopted is a fundamental step for the success of weed management. Among the methods, the chemical is the most used because of its efficiency and low cost. However, the use of this method in sesame crops is limited due to the scarcity of information on the selectivity and efficiency of herbicides for this crop. In this sense, the objective of this work was to determine the time of weed intervention, efficacy and the selectivity of herbicides applied in pre-emergence in the control of weeds in the sesame crop. In Chapter I, two experiments were conducted for two sesame cultivars, BRS Silk and CNPA G2 between 2016 and 2017 to determine PCPI. The experiments were conducted in a randomized block design with three replicates. The PCPI for cultivar BRS Silk is on average 78 and 67 days, whereas for CNPA G2 it is on average 63 and 52 days, considering, respectively, a loss of 2.5 and 5.0%. The cultivar CNPA G2 has a higher competitive capacity than the cultivar BRS Seda. Weed control for the BRS Silk cultivar should begin between the 10th and 12th day, whereas for the CNPA G2 it is between the 15th and 17th day, considering respectively a loss of 2.5 and 5.0%. In Chapter II, two experiments were conducted, one to determine the efficiency and the other to determine the selectivity of herbicides applied in pre-emergence in the year 2017. The experiments were conducted in a andomized complete block design with four replicates. The treatments were constituted by seven herbicides: diuron, flumioxazin, linuron, metalachor, metribuzin, metribuzin + oxyfluorfen, oxadiazon, oxyfluorfen applied in pre-emergence and two treatments, weeded and unhedged. The herbicides diuron and flumioxazin are selective for the pre-emergence sesame crop. The herbicide metribuzin caused high toxicity to sesame plants and did not control weed species. The metalachor did not cause high intoxication of the sesame, however, this herbicide reduces the productivity of the crop
Interfering periods and chemical weed control in sesame (Sesamum indicum L.)
Keywords: Competição; Herbicidas; Pré-emergência; Produtividade; Oleaginosas; Competition; Herbicides; Pre-emergence; Productivity; Oilseeds; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA